2004
DOI: 10.4018/jgim.2004070104
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences, Information and Code Systems

Abstract: This paper explores an alternative way of framing information systems research on the role and impact of national culture. It argues that the widely accepted structural framework of Hofstede reduces interpretation to a simplistic categorical description which in many cases ignores differentiation within cultures. The alternative model suggests, that national culture can be better understood by seeking out the dominant codes that frame the discourse pervasive in a culture and understanding how that discourse af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Inevitably risks are involved when global development challenges traditional cultural values, and the research for this paper suggests that unfortunately Vietnamese culture creates more resistance to the emergence of a knowledge society than those other cultural features which facilitate it. Some recent research in the area knowledge management addresses the role of social and cultural aspects of knowledge, but in the literature those concerns are limited to organizations, or if national culture is mentioned, they are seen as fixed across nation states and over time (Corbitt et al, 2004;Walsham, 2002). In contrast, our approach reveals great levels of tension and dynamism in Vietnam.…”
Section: Culture Knowledge and Developmentmentioning
confidence: 99%
“…Inevitably risks are involved when global development challenges traditional cultural values, and the research for this paper suggests that unfortunately Vietnamese culture creates more resistance to the emergence of a knowledge society than those other cultural features which facilitate it. Some recent research in the area knowledge management addresses the role of social and cultural aspects of knowledge, but in the literature those concerns are limited to organizations, or if national culture is mentioned, they are seen as fixed across nation states and over time (Corbitt et al, 2004;Walsham, 2002). In contrast, our approach reveals great levels of tension and dynamism in Vietnam.…”
Section: Culture Knowledge and Developmentmentioning
confidence: 99%
“…Culture has been defined differently based on several perspectives but Hofstede [24] has provided an in-depth discussion on culture and the various dimension of culture which have been widely accepted and used in a variety of disciplines [25,26] and validated directly or indirectly by many other researches in different settings [27].…”
Section: Refinement Of Technology Acceptance Modelsmentioning
confidence: 99%
“…Cultural Factors. Hofstede [24] has provided an in-depth discussion on culture and the various dimension of culture which have been widely accepted and used in a variety of disciplines (25,26].…”
Section: Applied Mechanics and Materials Vols 263-266mentioning
confidence: 99%
“…While studies have generally shown an effect of culture on individual behaviors and preferences, these effects are not systematic across situations and technologies. This may be a function of the level at which culture is defined and measured (Corbitt et al, 2004;Karahanna et al, 2002;Karahanna et al, 2008). Finding the right granularity for understanding culture is difficult relative to IT and development.…”
Section: Culturementioning
confidence: 99%